Nonstationary wave processes in the spherical shell—two-layer soil medium system - Meish, V.F.; Meish, Yu.A. (Reports of the National Academy of Sciences of Ukraine, 2018)
Nonstationary processes of propagation of spherical waves in the spherical shell—two-layer soil medium system are considered. Each layer of the soil medium is described within the framework of the behavior of a threecomponent soil medium, according to the equations of continuum mechanics. To solve these problems, the Mac-Cormack finite-difference scheme is used. The regularities of propagation of pressure waves in this system are given.